The Influence of Work Discipline, Islamic Work Motivation, and Compensation on Employee Performance: (Case Study at CV Lestari Albasia Mandiri) - Zeva Ega Sekarrisma; Nurudin Nurudin; Naili Saadah (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
Purpose - this study aims to determine the effect of work discipline, Islamic work motivation, and compensation on employee performance. Methods - this study uses a quantitative approach. Data collection was conducted through questionnaires with a sample of 138 people calculated using the slovin formula from a total population of 210 employees. The sample was determined using purposive sampling technique. Data were analyzed using SPSS 25 software. Result - The results showed that work discipline, Islamic work motivation, and compensation have a positive and significant effect on employee performance partially or simultaneously. Implications - this study can have implications for the development of science, as well as provide input to the management of CV Lestari Albasia Mandiri in making decisions related to employee performance.